Energy, economic and environmental modelling for supporting strategic local planning. (2017) - Becchio, Cristina; Bottero, Marta C.; Casasso, Alessandro; Corgnati, Stefano P.; Dell'Anna, Federico; Piga, Bruno; Sethi, Rajandrea
Abstract: This study investigates the use of an evaluation model able to estimate the possibilities of reducing energy consumption and emissions of the building sector exploiting renewable energy sources. Specific attention is given to the use of ground source heat pumps in the urban context, proposing an ex-ante evaluation of different scenarios to identify the most balanced one in terms of energy, economic and environmental effects. The model is applied to a case study in Northern Italy to show how it can be used to support local administrations in energy urban planning, fitting economically and environmentally sustainable technologies. Moreover, it defines new boundaries in which the energy and environmental analyses should be carried out (spatial relocation), and the time span over which impacts have to be evaluated (temporal relocation).